2023
DOI: 10.1039/d2ce01590k
|View full text |Cite
|
Sign up to set email alerts
|

Structural and mechanistic studies of excitation- and temperature-tunable multicolor luminescence of triarylborane

Abstract: The development of single-component organic systems with different phosphorescent behaviors remains a formidable challenge. Herein, an organic triarylborane has been synthesized, (3-bromo-2-(phenylethynyl)phenyl)dimesitylborane (1), which can be obtained as racemate (rac-1)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 77 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…8 So far, only limited success was achieved for single-component small molecule crystals. 5 a ,9 Favereau et al reported that the excitation-dependent fluorescence–phosphorescence (ExDFPh) dual emission of an enantiopure cyclohexane- trans -1,2-bisphthalimide derivative is associated with two different emission origins. The RTP originates from the electron transition of single molecules, while the fluorescence is from the H-aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…8 So far, only limited success was achieved for single-component small molecule crystals. 5 a ,9 Favereau et al reported that the excitation-dependent fluorescence–phosphorescence (ExDFPh) dual emission of an enantiopure cyclohexane- trans -1,2-bisphthalimide derivative is associated with two different emission origins. The RTP originates from the electron transition of single molecules, while the fluorescence is from the H-aggregates.…”
Section: Introductionmentioning
confidence: 99%